Determinants of Profitability in Commercial Banks Listed on the Indonesian Stock Exchange - M Kemal Attatur; Ahmad Gymyastiar; Henny Setyo Lestari (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to examine the impact of Bank size, including asset size and deposit size, capital adequacy, credit quality, liquidity, inflation, and Gross Domestic Product growth on Bank profitability, as measured by Return n Assets and Return on Equity. Focusing on a sample of commercial Banks listed on the Indonesia Stock Exchange from 2019 to 2023, this study uses purposive sampling with 41 Banks over a five-year period. Data analysis was performed using descriptive statistics and random effects models through panel data regression in E-views 9.0. The results showed that asset size has a significant positive effect on Return on Assets and Return on Equity. Deposit size, capital adequacy, credit quality, and Gross Domestic Product growth do not have a significant impact on profitability, Liquidity does not have a significant effect on Return on Equity but shows a positive impact that is almost significant on Return on Assets. Inflation has a significant positive effect on Return on Equity but not on Return on Assets. Based on these findings, it is recommended that Banks focus on managing asset size and monitoring inflation trends to improve profitability. Further research is suggested to include additional variables and extend the sample period for a more comprehensive understanding of the determinants of Bank profitability.